Lampyroidea maculata (Coleoptera: Lampyridae): A new species of lampyrid from Iran - Geisthardt, Michael; Day, John C. (Zootaxa, 2004)
A new lampyrid species, Lampyroidea maculata sp. nov., is described from Northern Iran. This is the third species of this genus from Iran and the new species is compared with both Lampyroidea antennalis Geisthardt, 1988 and Lampyroidea persica Olivier, 1907.